Statins and Major Adverse Limb Events in Patients with Peripheral Artery Disease: A Systematic Review and Meta-Analysis - Pastori, Daniele; Farcomeni, Alessio; Milanese, Alberto; Del Sole, Francesco; Menichelli, Danilo; Hiatt, William R.; Violi, Francesco (Thrombosis and Haemostasis, 2020)
Background Statins are guidelines recommended in patients with peripheral artery disease (PAD) for the prevention of cardiovascular (CV) events. Comprehensive meta-data on the impact of statins on major adverse limb events (MALE) in PAD patients are lacking. We examined the association of statin use with MALE in patients with PAD.Methods We performed a systematic review (registered at PROSPERO: number CRD42019137111) and metanalysis of studies retrieved from PubMed (via MEDLINE) and Cochrane (CENTRAL) databases addressing the impact of statin on MALE including amputation and graft occlusion/revascularization. Secondary endpoints were all-cause death, composite CV endpoints, CV death, and stroke.Results We included 51 studies with 138,060 PAD patients, of whom 48,459 (35.1%) were treated with statins. The analysis included 2 randomized controlled trials, 20 prospective, and 29 retrospective studies. Overall, 11,396 MALE events, 21,624 deaths, 4,852 composite CV endpoints, 4,609 CV deaths, and 860 strokes were used for the analysis. Statins reduced MALE incidence by 30% (pooled hazard ratio [HR]: 0.702; 95% confidence interval [CI]: 0.605–0.815) and amputations by 35% (HR: 0.654; 95% CI: 0.522–0.819), all-cause mortality by 39% (pooled HR: 0.608, 95% CI: 0.543–0.680), CV death by 41% (HR: 0.594; 95% CI: 0.455–0.777), composite CV endpoints by 34% (pooled HR: 0.662; 95% CI: 0.591–0.741) and ischemic stroke by 28% (pooled HR: 0.718; 95% CI: 0.620–0.831).Conclusion Statins reduce the incidence of MALE, all-cause, and CV mortality in patients with PAD. In PAD, a high proportion of MALE events and deaths could be prevented by implementing a statin prescription in this patient population.
Keywords: statin; peripheral artery disease; major adverse limb event; stroke; amputation; cardiovascular death; all-cause death